2010
DOI: 10.2217/pgs.10.93
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipid-Lowering Drugs on Reverse Cholesterol Transport Gene Expressions in Peripheral Blood Mononuclear and Hepg2 Cells

Abstract: Aims:The ATP-binding cassette transporters, ABCA1 and ABCG1, are LXR-target genes that play an important role in reverse cholesterol transport. We examined the effects of inhibitors of the cholesterol absorption (ezetimibe) and synthesis (statins) on expression of these transporters in HepG2 cells and peripheral blood mononuclear cells (PBMCs) of individuals with primary (and nonfamilial) hypercholesterolemia (HC). Materials & methods:A total of 48 HC individuals were treated with atorvastatin (10 mg/day/4 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 45 publications
2
11
0
1
Order By: Relevance
“…Our data are also consistent with previous findings that short-term treatment with low-dose atorvastatin decreased ABCA1 and ABCG1 mRNA expression in blood cells of hypercholesterolemic patients [23]. In addition, more recent studies using HDL as the lipid acceptor to evaluate ABCG1-mediated cholesterol efflux have shown that simvastatin and atorvastatin reduce cholesterol efflux in human macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are also consistent with previous findings that short-term treatment with low-dose atorvastatin decreased ABCA1 and ABCG1 mRNA expression in blood cells of hypercholesterolemic patients [23]. In addition, more recent studies using HDL as the lipid acceptor to evaluate ABCG1-mediated cholesterol efflux have shown that simvastatin and atorvastatin reduce cholesterol efflux in human macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…Blood was diluted in phosphate buffered saline (1:1) and this suspension was layered in Hystopaque-1077 (Sigma-Aldrich, MO, USA) and centrifuged for 30 min at 400 × g at room temperature. PBMC were collected from the interphase and immediately used for RNA extraction [16].…”
Section: Blood Samples and Isolation Of Mononuclear Cellsmentioning
confidence: 99%
“…We have previously shown that lipid-lowering drugs can infl uence the expression of two important genes involved in the HDL metabolism, ABCA1 and ABCG1 , in a cell-specifi c manner (5) . According to our fi ndings, atorvastatin, simvastatin or ezetimibe treatment downregulated ABCA1 and ABCG1 mRNA expression in peripheral blood mononuclear cells of hypercholesterolemic individuals, even in the absence of changes in serum HDL-C or apolipoprotein AI (apoAI), the major protein of HDL.…”
mentioning
confidence: 99%